2016
DOI: 10.1016/j.nlm.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic neurodegeneration in an Alzheimer mouse model overexpressing amyloid-precursor protein with the Swedish-Dutch-Iowa mutations

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder that is mainly characterized by beta-amyloid (Aβ) plaque deposition, Tau pathology and dysfunction of the cholinergic system causing memory impairment. The aim of the present study was to examine (1) anxiety and cognition, (2) Aβ plaque deposition and (3) degeneration of cholinergic neurons in the nucleus basalis of Meynert (nbM) and cortical cholinergic innervation in an Alzheimer mouse model (APP_SweDI; overexpressing amyloid precursor protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Cognitive impairment along with anxiety in AD animal models, which resembles that in AD patients, has been reported (Foidl et al , 2016; Pietrzak et al , 2015; Sil and Ghosh, 2016; Starkstein et al , 2007). Protofibrillar Aβ 1–42 injection induced anxiety and AD-like pathology in rats (Sharma et al , 2016), suggesting the deleterious effect of elevated Aβ levels on behavior in AD.…”
Section: Discussionmentioning
confidence: 97%
“…Cognitive impairment along with anxiety in AD animal models, which resembles that in AD patients, has been reported (Foidl et al , 2016; Pietrzak et al , 2015; Sil and Ghosh, 2016; Starkstein et al , 2007). Protofibrillar Aβ 1–42 injection induced anxiety and AD-like pathology in rats (Sharma et al , 2016), suggesting the deleterious effect of elevated Aβ levels on behavior in AD.…”
Section: Discussionmentioning
confidence: 97%
“…This process of neurodegeneration is triggered by the accumulation of Aβ peptide [5] , which have also been hypothesized to induce neurodegenerative changes at cholinergic terminals [6] . Additionally, other studies revealed that oligomeric Aβ induces cell death [7] , encourages apoptosis by physically piercing the cell membrane, causes neurotoxic cascade and neurodegeneration that leads to AD [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…ROS are catalyzed by a combination of redox active metal ions and Aβ in AD [ 4 ]. Severe damage to the cholinergic system, including decreased choline uptake and reduced choline acetyltransferase (ChAT) activity, have been noted in AD patients; meanwhile, the damaged cholinergic system may be further responsible for Aβ plaque formation and increasing phosphorylation of tau protein [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%